Bifidobacteria and humans: our special friends, from ecological to genomics perspectives. (16th September 2013) - Ventura, Marco; Turroni, Francesca; Lugli, Gabriele Andrea; van Sinderen, Douwe
Abstract Bifidobacteria are widely used as health‐promoting microorganisms in many functional foods. However, the molecular mechanisms as to how these bacteria positively impact on host health are far from completely understood. For this reason these bacteria constitute a growing area of scientific interest with respect to their genomics, molecular biology and genetics. Genome sequencing of an increasing number of strains of bifidobacteria has provided access to the complete genetic make‐up of many representative members of these bacteria. The aim of this review is to highlight the genetic and functional features of bifidobacteria residing in the human gastrointestinal tract using genomic and ecology‐based information. © 2013 Society of Chemical Industry